Lovesick Japan : Sex * Marriage * Romance * Law - West, Mark D., 1968- (Book collections on Project MUSE., 2011)
This book explores an official vision of love, sex, and marriage in contemporary Japan. A comprehensive body of evidence-2,700 court opinions-describes a society characterized by a presupposed absence of physical and emotional intimacy, affection, and personal connections. In compelling, poignant, and sometimes horrifying court cases, West finds that Japanese judges frequently opine on whether a person is in love, what other emotions a person is feeling, and whether those emotions are appropriate for the situation.